REVIEW OF SCHEFFLER REFLECTOR - Mr. Aniket M. Akhade; Dr. Rupesh J. Patil (International Journal of Innovations in Engineering Research and Technology, 2021)
Scheffler reflector is one of the various methods of harvesting the solar energy. Sche ffl er fixed focus concentrators are successfully used for medium temperature applications in different parts of the world. These concentrators are taken as lateral sections of paraboloids and provide fixed focus away from the path of incident beam radiations throughout the year. Parabolic Scheffler Reflectors can provide us high temperature heat for all types of cooking, steam generation and many other applications. In this paper different Scheffler systems are reviewed.